KELENGKAPAN BERKAS PERSYARATAN KLAIM BPJS PADA PASIEN RAWAT INAP DI RUMAH SAKIT WAVA HUSADA MALANG: PERSYARATAN KLAIM BPJS - Ulum, Miftachul (Malang: Sekolah Tinggi Ilmu Administrasi Malang, 2024)
The completeness of medical record file information is very important for verification of claims. Verification of claims is specially prepared with the aim of being a reference verifier of claims on BPJS. Completeness of medical records also maintains health facilities for service quality and efficiency of health service costs up to the disbursement of claims to health care providers. The purpose of this report is to find out the Completeness of BPJS claim requirements for inpatients at Wava Husada Hospital in 2022 with an observation method in the form of a checklist conducted on March 21-March 26, 2022. This research was conducted at the Health Financing Cooperation Installation and Casemix. Based on the results of the completeness analysis on 120 BPJS claim requirements files conducted by researchers, a completeness percentage of 75 files or 62.5% and a percentage of incompleteness of 45 files or 37.5%. The highest completeness is found in the inpatient cover letter, participant egibility letter (SEP), emergency assessment sheet, and medical support sheet with a completeness rate of 120 files or 100% and the lowest completeness is found on the casemix verification sheet of 102 files or 85%. As for overcoming this, it is recommended to hold a coordination meeting with health service providers regarding the importance of completeness and accuracy of filling out medical record files for BPJS claim requirements, to facilitate the process of submitting hospital claims to BPJS.